BOBOT BADAN DAN PERTAMBAHAN BOBOT BADAN AYAM KAMPUNG PERIODE STARTER PADA KETINGGIAN TEMPAT BERBEDA - Rajab Rajab (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
Phisical environment such as climate and attitude of place were the important factors effect on production performance of broiler, layer, or domectic fowl. The purpose of this research was to know the effect of altitude on body weight and average daily gain of native fowl breeded at starter period. The research was conducted at Waringin Cap area (highland of attitude place) and Air Alii Area (lowland of attitude place), which 106 tail of native fowl were rearing in intersive poultry farming system. DOC were placed on brooder box cage with 2 x 1 x 1 of size. The variables such as body weight and average daily gain were measured every week during 4 week observation. The results of this study show that both the average of body weight of hen in Waringin Cap were 30,70 ; 46,48; 131,44; 248,44 dan 329,98 g, whereas the average of body weight of hen in Air Alii were 30,98; 47,34; 139,45; 254,21 dan 348,81 g respectively for one day, 1, 2, 3, and 4 weeks of age. The average daily gain rate were 0,22 – 0,40 and 0,32 – 0,52 g/tail/day respectively for chicken in highland and lowland attitude rearing. and there are no significantly different of the attitude effect on native fowl performance breeded at starter period.